Establishing a statistical relation between meteorological and hydrological drought indices - M. A. Jincy Rose; N. R. Chithra (Water Supply, 2022)
Investigation of the hydrological drought behaviour of the Bharathapuzha river basin of Kerala, India, on account of the meteorological drought condition of the watershed was carried out in this study with the aid of four popular drought indices. Statistical relations were established between the indices using polynomial regression models to help in predictions. A study on the decadal spatial variation of hydrological drought behaviour over the basin was also conducted. The cross-correlation study was also performed to understand the propagation of hydrological drought in the event of meteorological drought. The results reveal a slight decrease in the spatial extent of hydrological drought over time. The correlation between meteorological and hydrological drought indices was found to be more assertive at grid locations G1 and G4. According to the findings, the strongest correlation of 0.8 in the propagation of meteorological to hydrological drought was observed at a lag of 3 months over a 12 -month timescale. Run theory reveals that the river basin is subjected to hydrological drought over 54–65% of the months in the historic period. Regression analysis suggests that the cubic model outperforms the other models. HIGHLIGHTS Four distinct drought indices were used to identify drought characteristics.; Spatiotemporal drought patterns were analysed in a tropical river basin in Kerala, India.; The propagation of meteorological to hydrological drought was obtained through a cross-correlation study.; Establishes a statistical relation between meteorological and hydrological drought indices.;